Complicated gratitude: a letter to my mother’s physician - Cooper, Rachel B. (Canadian Medical Association journal (CMAJ), 2020)
Cooper thanks the physician who administered medical assistance in dying to her mother. The physician relieved her mother of the endless breathlessness caused by her endstage chronic obstructive pulmonary disease. He enabled her to rest and slumber peacefully for the first time in months, if not years. He fulfilled his professional duties ethically, within the parameters of the legislation. He allowed her mother to have a good death. An ethical death. A compassionate death, free of the suffering she experienced in life.